Publisher correction: Re-analysis of public genetic data reveals a rare X-chromosomal variant associated with type 2 diabetes (vol 9, 321, 2018) - Bonas-Guarch,S; Guindo-Martinez,M; Miguel-Escalada,I; Grarup,N; Sebastian,D; Rodriguez-Fos,E; Sanchez,F; Planas-Felix,M; Cortes-Sanchez,P; Gonzalez,S; Timshel,P; Pers,TH; et al. (Nature Communications, 2018)
Correction to:Nature Communicationshttps://doi.org/10.1038/s41467-017-02380-9, published online 22 January 2018In the originally published version of this Article, the affiliation details for Santi González, Jian’an Luan and Claudia Langenberg wereinadvertently omitted. Santi González should have been affiliated with 'Barcelona Supercomputing Center (BSC), Joint BSC-CRG-IRBResearch Program in Computational Biology, 08034 Barcelona, Spain’, and Jian’an Luan and Claudia Langenberg should have beenaffiliated with‘MRC Epidemiology Unit, University of Cambridge School of Clinical Medicine, Cambridge Biomedical Campus,Cambridge CB2 0QQ, UK’. Furthermore, the abstract contained an error in the SNP ID for the rare variant in chromosome Xq23,which was incorrectly given as rs146662057 and should have been rs146662075. These errors have now been corrected in both the PDFand HTML versions of the Article.